The Application of the Problem Based Learning (PBL) Model in Enhancing Critical Thinking Skills and Learning Outcomes of Students in the Equal Education Program - Wati, Maini (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2026)
Education is an essential basic need for every individual and serves as the main foundation in the formation of quality human resources. Thru education, an individual not only acquires knowledge and skills but also internalizes moral and social values, as well as critical thinking abilities that are essential for facing life's challenges. However, the reality shows that the opportunity to obtain formal education is still not evenly distributed due to economic, social, and geographical factors. To bridge this gap, the Indonesian government organizes the Equivalency Education Program as part of the non-formal education pathway, which includes Package A, Package B, and Package C. This program aims to provide learning opportunities equivalent to formal education while also developing critical thinking skills and ensuring that students' learning outcomes are relevant to real-life needs. In practice, the implementation of equivalency education still faces various obstacles, especially in terms of teaching methods. The learning process, which tends to be conventional and educator-centered, results in low active participation and critical thinking skills among students. To address these issues, more contextual and participatory learning innovations are needed, one of which is the Problem Based Learning (PBL) model. This model emphasizes authentic problem-based learning, encouraging students to analyze, collaborate, and independently and reflectively find solutions. This study uses a descriptive qualitative approach with the aim of illustrating the implementation of PBL in enhancing critical thinking skills and learning outcomes of students in equivalency education programs. The conceptual review results indicate that the implementation of PBL has a positive impact on the improvement of critical thinking skills and learning outcomes in cognitive, affective, and psychomotor aspects. Thus, the application of the PBL model is considered effective and relevant in the context of equivalency education because it aligns with the principles of andragogy, contextual learning, and the development of lifelong learning.